Towards management of Musa nematodes in Asia and the Pacific - Country reports: Country reports of the training workshop on enhancing capacity for nematode management in small-scale banana cropping systems held at the Institute of Plant Breeding, University of the Philippines Los Baños Laguna, Philippines, 1-5 December 2003. - Cruz, F.S. de la; Bergh, Inge van den; Waele, D. de; Hautea, D.M.; Molina, A.B. (2005)
The country status reports are published in the accompanying proceedings of this technical manual.